Enhanced Performance of CAP-Modulated Visible Light Communication System Utilizing Geometric Shaping and Rotation Coding - Fangchen Hu; Peng Zou; Guoqiang Li; Weixiang Yu; Nan Chi (IEEE Photonics Journal, 2019)
Aiming to improve the performance of free space visible light communication (VLC) system, we combined the use of rotation coding together with geometric shaping (GS) technology in carrierless-amplitude-and-phase (CAP) modulation visible light communication system. In this paper, we designed a new GS-16QAM constellation named Triangular. Triangular GS-16QAM has a better noise resistance due to its larger value of the minimum Euclidean distance. Based on the excellent new 16QAM constellation, we further improve the performance of VLC system utilizing a proposed new coding technology named rotation coding after the quadrature-amplitude-modulation (QAM) mapping. The rotation coding can reduce the overlapping problem of the outer constellation points induced by non-linear impairment. Finally, the upper gain about 1 dB is achieved with rotation coding in 1.2 m free space VLC communication when the transmission speed is relatively low about 80 Mb/s. While the transmission speed is relatively high around 2 Gb/s in CAP-VLC system, Triangular constellation with rotation coding still has positive effect for transmission quality with about 1 dB enhancement than the square 16QAM. All of these results are verified by simulations and experiments.